2019
DOI: 10.1016/j.bbi.2019.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Stressful life events, inflammation and emotional and behavioural problems in children: A population-based study

Abstract: Objective: To test the hypothesis that higher plasma levels of inflammatory markers due to exposure to adverse life events may lead to internalising and externalising symptoms in children. Method: Using data from the Avon Longitudinal Study of Parents and Children, a general population birth cohort, we explored if inflammatory markers [serum C-reactive protein (CRP) and interleukin-6 (IL-6)] at age 9 years explain the longitudinal association between adverse life events (at ages 1-9 and 9-11 years) and interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 35 publications
(35 reference statements)
2
26
0
Order By: Relevance
“…Telomeres shorten with every cell division, and telomeres that are shortened past a critical length can become senescent (Harley et al, 1990). These senescent cells can exert harmful effects on the tissue micro-environment, including an increase in the secretion of pro-inflammatory cytokines (Davalos, Coppe, Campisi, & Desprez, 2010), which in turn could impact brain functioning and behavior (Flouri, Francesconi, Papachristou, Midouhas, & Lewis, 2019). Alternatively, as our present study did not include an earlier measure of behavior problems, it is also possible that telomeres do not contribute to the development, but are a result, of behavior problems.…”
Section: Discussionmentioning
confidence: 99%
“…Telomeres shorten with every cell division, and telomeres that are shortened past a critical length can become senescent (Harley et al, 1990). These senescent cells can exert harmful effects on the tissue micro-environment, including an increase in the secretion of pro-inflammatory cytokines (Davalos, Coppe, Campisi, & Desprez, 2010), which in turn could impact brain functioning and behavior (Flouri, Francesconi, Papachristou, Midouhas, & Lewis, 2019). Alternatively, as our present study did not include an earlier measure of behavior problems, it is also possible that telomeres do not contribute to the development, but are a result, of behavior problems.…”
Section: Discussionmentioning
confidence: 99%
“…15 Thus, the link from early stressful life events to depression via inflammation is plausible but, to our knowledge, still unexplored in adolescence. One study tested the role of inflammation in the association between stressful life events and internalising symptoms, but did not investigate links beyond childhood, did not consider the role of prenatal life events and did not explore depressive symptomatology specifically 49 . No study has yet investigated if prenatal and childhood stressful life events are related to the development of depression across adolescence via increasing levels of inflammatory markers.…”
Section: Introductionmentioning
confidence: 99%
“…However, IL-6 did not explain the association between ELA and externalizing symptoms. A separate study on this cohort found that IL-6 levels at 9 years partially mediated the association between ELA in childhood and depressive symptoms at the beginning of adolescence (Flouri et al, 2019). Internalizing symptoms at age 9 years fully mediated the association between levels of IL-6 in childhood and subclinical psychotic symptoms (psychotic-like experiences, PLEs) at age 18 (Flouri et al, 2020).…”
Section: Research Questionsmentioning
confidence: 91%
“…However, childhood sexual abuse was significantly associated with IL-6 and CRP for nonwhites only (Pinto Pereira et al, 2019). In studies of pediatric populations, threat experiences of maltreatment and victimization are positively associated with inflammation in some studies (Baldwin et al, 2018; Bucker et al, 2015; Danese et al, 2007; Flouri et al, 2019; Kilic et al, 2017) but not all (Bernard et al, 2019; Cicchetti et al, 2015; Miller & Cole, 2012).…”
Section: Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation